Interregional interaction in ancient Mesoamerica - Englehardt, Joshua D., editor; Carrasco, Michael D., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
Explores the role of interregional interaction in dynamic sociocultural processes that shaped the Pre-Columbian societies of Mesoamerica. Interdisciplinary scholars examine linguistic exchange and borrowing, scribal practices, settlement patterns, ceramics, iconography, and trade systems, presenting a variety of case studies drawn from multiple spatial, temporal, and cultural contexts.--Provided by publisher.
Interaction and the making of ancient Mesoamerica / Joshua D. Englehardt and Michael D. Carrasco -- The prehispanic Mesoamerican world: framing interaction / Gary M. Feinman -- Interaction and exchange in early formative western and central Mesoamerica: new data from coastal Oaxaca / Guy David Hepp -- The role of interregional interaction in Mesoamerican script development / Joshua D. Englehardt and Michael D. Carrasco -- Hieroglyphic Ch'olan to Ch'orti': tracing linguistic and social interactions into eastern Ch'olan / Kerry M. Hull -- Reframing the tripod: a foreign form adopted by the early classic Maya / Bryan Schaeffer -- Across the hills, towards the ocean: Teotihuacan/style monuments in Guerrero, Mexico / Jesper Nielsen, Elizabeth Jimenez García, and Iván Rivera -- A sprinkling of culture: contact and connections between the Tuxtlas Region and the coastal Maya / Philip J. Arnold III and Lourdes Budar -- Variation and similarity in obsidian tool styles and technologies at the Zaragoza/Oyameles source area, Puebla, Mexico / Charles L.F. Knight -- Interregional interaction in northwest Mesoamerica during the Classic and Postclassic periods / Jose Luis Punzo Díaz -- Round and round we go: Cholula, rotating power structures, social stability, and trade in Mesoamerica / Timothy J. Knab and John M.D. Pohl -- The movement of metal goods in the Mesoamerican late Postclassic period: a case study from the Templo mayor in Tenochtitlan / Niklas Schulze and Blanca E. Maldonado -- Competitive vs. peaceful interaction / Joyce Marcus -- Conclusion: the world as they knew it: the interaction sphere concept in current Mesoamerican archaeology / David Freidel.
Keywords: Social archaeology -- Central America; Social archaeology -- Mexico; Indians of Central America -- Antiquities; Indians of Mexico -- Antiquities; Indians of Central America -- Social conditions; Indians of Mexico -- Social conditions; Central America -- Antiquities; Mexico -- Antiquities